2005
DOI: 10.1063/1.2133902
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties and leakage current characteristics of Bi3.25La0.75Ti3O12 thin films prepared by the polymeric precursor method

Abstract: The ferroelectric properties and leakage current mechanisms of preferred oriented Bi 3.25 La 0.75 Ti 3 O 12 ͑BLT͒ thin films deposited on La 0.5 Sr 0.5 CoO 3 by the polymeric precursor method were investigated. These films showed excellent ferroelectric properties in terms of large remnant polarization ͑2P r ͒ of 47.6 C/cm 2 and ͑2E c ͒ of 55 kV/ cm, fatigue-free characteristics up to 10 10 switching cycles, and a current density of 0.7 A/cm 2 at 10 kV/ cm. X-ray diffraction and scanning electron microscope in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…To reduce the surface energy, the primary particles have a tendency to form nearly spherical agglomerates, in a minimum surface to volume ratio and hence reducing surface free energy [29,28]. This type of grain structure is common in oxide, ferrite and titanate ceramics [30][31][32][33][34][35][36][37]. This is a result of an abnormal/discontinuous grain growth and also called an exaggerated grain growth.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the surface energy, the primary particles have a tendency to form nearly spherical agglomerates, in a minimum surface to volume ratio and hence reducing surface free energy [29,28]. This type of grain structure is common in oxide, ferrite and titanate ceramics [30][31][32][33][34][35][36][37]. This is a result of an abnormal/discontinuous grain growth and also called an exaggerated grain growth.…”
Section: Resultsmentioning
confidence: 99%
“…potential candidates for ferroelectric energy storage. [104][105][106] Lou et al have first put BLT systems into practice for improving the lead-free systems' energy storage performances by preparing the Bi 3.25 La 0.75 Ti 3 O 12 (BLT) thick films on Pt/Ti/SiO 2 / Si wafers using chemical solution deposition (CSD), as shown in Figure 14a. By means of changing annealing temperature, excellent ESD of 47.7 J cm −3 with goodish fatigue behavior has been obtained in BLT thick film for the slim P-E loop, which is attributed to the effects of small crystallite.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…The leakage current -voltage (or electric field) characteristics showed the Ohmic behaviour. This conduction mechanism has been observed in many samples when the samples were measured in low voltage region such as Wu et al [15] observed the same conduction mechanism in YMnO 3 thin films prepared on (001) GaN substrates by pulsed laser deposition, and Simões et al [16] observed this conduction mechanism in Bi 3.25 La 0.75 Ti 3 O 12 thin films deposited on La 0.5 Sr 0.5 CoO 3 by the polymeric precursor method. The Ohmic conduction mechanism described above can also be used to explain the experimental results of Fig.…”
Section: Experimental Methodsmentioning
confidence: 72%